1996
DOI: 10.1056/nejm199604183341601
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor Compared with Expectant Management for Prelabor Rupture of the Membranes at Term

Abstract: In women with prelabor rupture of the membranes at term, induction of labor with oxytocin or prostaglandin E2 and expectant management result in similar rates of neonatal infection and cesarean section. Induction of labor with intravenous oxytocin results in a lower risk of maternal infection than does expectant management. Women view induction of labor more positively than expectant management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
244
5
16

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(290 citation statements)
references
References 7 publications
12
244
5
16
Order By: Relevance
“…These results are in agreement with results obtained by Ngai et al and was supported with similar finding obtained by Javaid et al and Lee et al [3][4][5] In the present study, about 36% of patients in the expectant group went into spontaneous labour within 12 hours. These results are similar to the results obtained by Hannah et al (1996)6 and supported with similar finding obtained by Napgal et al and Shetty et al 7,8 Oxytocin was used in 18% of patients in the immediate induction group and in 44% of patients in the expectant management group for augmentation of labour after the onset of labour pain. This is similar to the results obtained by Chaudhuri Snehamay C et al who found that the rate of use of oxytocin during labor was 32.43% induction group and 82.14% in expectant group.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with results obtained by Ngai et al and was supported with similar finding obtained by Javaid et al and Lee et al [3][4][5] In the present study, about 36% of patients in the expectant group went into spontaneous labour within 12 hours. These results are similar to the results obtained by Hannah et al (1996)6 and supported with similar finding obtained by Napgal et al and Shetty et al 7,8 Oxytocin was used in 18% of patients in the immediate induction group and in 44% of patients in the expectant management group for augmentation of labour after the onset of labour pain. This is similar to the results obtained by Chaudhuri Snehamay C et al who found that the rate of use of oxytocin during labor was 32.43% induction group and 82.14% in expectant group.…”
Section: Resultssupporting
confidence: 91%
“…6 There were no significant differences in the neonatal complications between the two groups. These results are in accord with results obtained by Shetty et al and supported by results obtained by Javaid et al 4,8 These results are in accord with results obtained by Wing et al and reinforced by Shetty et al and supported by results obtained by Javaid et al 4,8,11 In the present study, the major causes of neonatal morbidity were neonatal sepsis, hyperbilirubinemia, respiratory distress syndrome and birth asphyxia.…”
Section: Resultsmentioning
confidence: 78%
“…In the case of active management of preterm rupture of membranes, the pooled random-effects odds (23) showed a large, statistically significant effect that was not apparent in any of the previous trials. In the case of elective induction of labor at term, the fixed-effect odds ratio for cesarean section changed from 0.40 to 0.84 between 1989 and 1992.…”
Section: Scatter and Predicted Range Of Relative Changes In The Treatmentioning
confidence: 65%
“…In the case of elective induction of labor at term, the fixed-effect odds ratio for cesarean section changed from 0.40 to 0.84 between 1989 and 1992. Subsequent trials, including a large one (23), have consistently given results showing a small benefit regarding this outcome. It is conceivable that the large treatment effect reported in the early trials may have been due to publication bias or publication lag (24).…”
Section: Scatter and Predicted Range Of Relative Changes In The Treatmentioning
confidence: 96%
“…3,4 If bishop score is less than 6 then cervix is considered unfavorable and its ripening is indicated prior to oxytocin infusion and artificial ruptured of a membranes to decrease failure rate of induction and risk of caesarean section. 5 Need of cervical ripening and induction should be considered when it is felt that the benefits of vaginal delivery out weight the potential fetal and maternal risk of induction. These issues should be discussed with the women in detail before initiation of induction.…”
Section: Introductionmentioning
confidence: 99%